Analisis Pengaruh Kualitas Produk Dan Lokasi Terhadap Impulse Buying Dengan Keputusan Pembelian Sebagai Variabel Intervening Pada Bana Central Park Ujung Gading - Yusmanita Yusmanita; Vicky Brama Kumbara; Putri Azizi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to test how much influence Product Quality and Location have on Impulse Buying with Purchasing Decisions as an Intervening Variable for Bana Central Park Ujung Gading Consumers. The data collection method is through surveys and distributing questionnaires, with unknown population size, and determining a sample of 97 respondents obtained from the Concran Sugiyono formula. The analytical method used is Structural Equation Modeling (SEM) using SmartPLS 3.0. The research results obtained show that there is a significant positive influence of product quality on purchasing decisions. There is a significant positive influence of location on purchasing decisions. There is a significant positive influence on product quality on Impulse Buying. There is an insignificant positive effect of location on impulse buying. There is a significant positive influence of Product Quality on Impulse Buying through Purchasing Decisions. There is a significant positive influence of location on impulse buying through purchasing decisions.